Análisis de la presencia de las multilatinas en el espacio económico del Grupo de Visegrád - Nedela, Daniel (Papeles de Europa, 2016)
This article aims to expand the still limited literature referred to multinational enterprises from Latin America. Existing works focus on the historical evolution that has allowed the process of multinationalisation of Latin-American companies and their emergence and configuration as worldwide references in their respective sectors. This paper analyzes the applicability and validity of existing theoretical frameworks for the process of internationalization of multilatinas in the region of Central Europe; particularly in the countries of the Visegrad Group.